2005
DOI: 10.1038/sj.bjc.6602571
|View full text |Cite
|
Sign up to set email alerts
|

Social and geographic disparities in access to reference care site for patients with colorectal cancer in France

Abstract: The aim of this study was to investigate the relationship between social and geographic characteristics and the type of care centre for initial colorectal surgery in France. Patients living far from a reference cancer site were less frequently treated in a reference cancer site than those who were living near a reference cancer site OR a ¼ (0.50 (0.33 -0.76)). As for topography and emergency presentation, place of residence (urban/rural), occupation and marital status were not associated with the type of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…In the light of concerns related to variations in health inequalities, an increasing number of studies have analysed distance to screening, radiation therapy utilization and other forms of cancer treatment in relation to survival rates (Bentham et al 1995;Hyndman et al 2000;Sheehan et al 2000;Bryant et al 2002;Dejardin et al 2005;French et al 2006;Pagano et al 2007). Variations in access to oncology centres have been studied as a potential explanatory factor for inequalities in patient survival from lung cancer in the South East of England (Jack et al 2003).…”
Section: Health Service Under Considerationmentioning
confidence: 99%
“…In the light of concerns related to variations in health inequalities, an increasing number of studies have analysed distance to screening, radiation therapy utilization and other forms of cancer treatment in relation to survival rates (Bentham et al 1995;Hyndman et al 2000;Sheehan et al 2000;Bryant et al 2002;Dejardin et al 2005;French et al 2006;Pagano et al 2007). Variations in access to oncology centres have been studied as a potential explanatory factor for inequalities in patient survival from lung cancer in the South East of England (Jack et al 2003).…”
Section: Health Service Under Considerationmentioning
confidence: 99%
“…Inequalities in access to appropriate care have been identified at international level as major issues in cancer care, due mainly to differences in socio-economic status [23], and geographical access to health care services [24]. In our Region, a study on colorectal cancer showed inequalities in access to hospital care associated with socio-economic status [25], and the distance between a patient's residence and the service supply seems relevant in activity planning [26].…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, a few French studies of colorectal cancer from a single cancer registry (Launoy et al, 1992;Desoubeaux et al, 1997) have suggested social inequalities in survival, underprivileged patients having poorer prognosis than more affluent patients. We recently suggested that access to specialised care was strongly associated with road distance to the nearest specialised centre especially for women and elderly patients (Dejardin et al, 2005). Recent research in different health-care systems also suggests a relationship between surgical volume and survival (Kee et al, 1999;Shrag et al, 2000;Platell et al, 2003).…”
mentioning
confidence: 99%